Revisiting the use of tawarruq as a means for liquidity: assessing fundamental concepts and prevalent applications - Sadique, Muhammad Abdurrahman (Serials Publications (P) Ltd, New Delhi, 2019)
Despite of its recognition in its basic form by several contemporary bodies of Islamic scholars, different types of tawarruq (monetization) offered by various Islamic banks remain a heavily discussed issue among scholars in the field. The basic objection to such modes is that the explicit aim being the obtaining of cash against undertaking a future debt for a higher amount, it could insinuate a riba based relationship, the transaction only acting as an unessential formality. The guidelines provided purport to ensure that the structure remains a valid trading mechanism by ensuring the presence of the vital ingredients common to all sales and purchases, especially that the buyer becomes the lawful owner of an identified asset fully entitled and able to utilize it in any way he pleases. The adverse perception coordinated tawarruq could generate regarding the reality of Islamic banking should not be underestimated. Relevant controls should be adopted so that the application of legitimate modes of financing advocated by Shari‘ah such as partnership and investment are not pushed even further away from realization by the widespread adoption of coordinated tawarruq.